2020
DOI: 10.1021/acsinfecdis.0c00263
|View full text |Cite
|
Sign up to set email alerts
|

Using a Fragment-Based Approach to Identify Alternative Chemical Scaffolds Targeting Dihydrofolate Reductase from Mycobacterium tuberculosis

Abstract: Dihydrofolate reductase (DHFR), a key enzyme involved in folate metabolism, is a widely explored target in the treatment of cancer, immune diseases, bacteria, and protozoa infections. Although several antifolates have proved successful in the treatment of infectious diseases, they have been underexplored to combat tuberculosis, despite the essentiality of M. tuberculosis DHFR (MtDHFR). Herein, we describe an integrated fragment-based drug discovery approach to target MtDHFR that has identified hits with scaffo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…Although fragments often bind weakly, they tend to bind to hotspot regions of the target, forming well defined interactions that allow subsequent elaboration into larger drug-like molecules [17] , [18] . Our group and a few others have pioneered using this approach against different mycobacterial species and different protein targets with varying degrees of success [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%
“…Although fragments often bind weakly, they tend to bind to hotspot regions of the target, forming well defined interactions that allow subsequent elaboration into larger drug-like molecules [17] , [18] . Our group and a few others have pioneered using this approach against different mycobacterial species and different protein targets with varying degrees of success [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 The structural similarities between amoxapine and loratadine, the lead compounds identified in our previous studies, suggested that screening low-molecular-weight compounds with similar structural features could help identify novel scaffolds with similar activities for further synthetic elaboration. 12 14 We assembled a small library of compounds that were enriched in fused aromatic scaffolds and evaluated their ability to inhibit MRSA growth in combination with a sublethal dose of oxacillin. Several candidate scaffolds emerged from this screen.…”
mentioning
confidence: 99%
“…Previously, we have disclosed the identification and study of two classes of U.S. Food and Drug Administration (FDA)-approved compounds that potentiated β-lactam antibiotics in methicillin-resistant Staphylococcus aureus (MRSA) by dampening the transcription of key resistance genes. , The structural similarities between amoxapine and loratadine, the lead compounds identified in our previous studies, suggested that screening low-molecular-weight compounds with similar structural features could help identify novel scaffolds with similar activities for further synthetic elaboration. We assembled a small library of compounds that were enriched in fused aromatic scaffolds and evaluated their ability to inhibit MRSA growth in combination with a sublethal dose of oxacillin. Several candidate scaffolds emerged from this screen.…”
mentioning
confidence: 99%
“…In 2020, an FBDD approach on DHFR was described [ 18 ]. The authors used the complex between a hit and DHFR as the starting point for further elaboration.…”
Section: Mtb Enzymatic Targetsmentioning
confidence: 99%